2019
DOI: 10.4236/ajps.2019.109113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Individual and Synergistic Antimicrobial Activity of Common Spices against Certain Infectious Pathogen in Bangladesh

Abstract: Aims: The aim of this undertaken investigation was designed to determine the comparative antimicrobial potential of ethanol extract of six commonly consumed spices such as Garlic (Allium satilyvum), Ginger (Zingiber officinale), Turmeric (Curcuma longa), Cinnamon (Cinnamomum zeylanicum), Cumin (Cuminum cyminum) and Black cumin (Nigella sativa). Method: This study includes, the efficacy of individual and synergistic effect of these extracts that was tested against bacteria by agar well-diffusion method employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The extracts displayed substantial activity against Escherichia coli and Salmonella typhi, with inhibition zones measuring up to 18.0 mm and 15.0 mm, respectively. This efficacy mirrors findings from other studies where Nigella sativa demonstrated significant antibacterial effects, further enhanced when combined with other substances such as turmeric (16). The ethanolic extract of black seeds also showed promising results against Bacillus cereus (17), indicating a broad spectrum of activity that may be beneficial in food preservation.…”
Section: Discussionsupporting
confidence: 84%
“…The extracts displayed substantial activity against Escherichia coli and Salmonella typhi, with inhibition zones measuring up to 18.0 mm and 15.0 mm, respectively. This efficacy mirrors findings from other studies where Nigella sativa demonstrated significant antibacterial effects, further enhanced when combined with other substances such as turmeric (16). The ethanolic extract of black seeds also showed promising results against Bacillus cereus (17), indicating a broad spectrum of activity that may be beneficial in food preservation.…”
Section: Discussionsupporting
confidence: 84%
“…The antibacterial potency of the essential oil and extracts of Z. zerumbet was determined using disc diffusion assay (Bajpai et al, 2009;Chowdhury et al, 2019;Fadli et al, 2012). Two Gram-negative bacteria (Escherichia coli (ATCC 25922) and Salmonella typhi (ATCC 14028)) as well as two Gram-positive bacteria (Staphylococcus aureus (ATCC 25923) and Bacillus cereus (ATCC 14579) were used as the tested bacterial strains.…”
Section: Antibacterial Assaymentioning
confidence: 99%